Variability in thickness measurements using X-ray fluorescence technique - Baltazar, Immaculada C.; Mena, Manolo G.
Thirty units of tin plated Dual In-line Packages were used to evaluate the measurement system for tin thickness using the X-ray Fluorescence technique. The results showed that the system is sensitive to inspector technique and the total measurement error estimate was about 22 microinches. This system for obtaining tin thickness measurements had been recommended only when the variability of the process is at least 80 microinches. Otherwise, a more sensitive method must be used.
Keywords: X-ray fluorescence technique